Resolution of Severe Neurologic Signs Following Intravenous Lipid Emulsion Therapy in a Young Dog With a Portosystemic Shunt: Case Report - Spillane, Amanda M.; Haraschak, Jenica L.; McMichael, Maureen A. (Frontiers in Veterinary Science, 2021)
A 5-month-old male intact Great Pyrenees was presented for an acute onset of severe neurologic signs (stupor, absent menace, intermittent torticollis and head turn to the left). The patient’s history included possible naproxen ingestion with a maximum ingested dose of 59 mg/kg, exceeding the reported dose of >50 mg/kg known to cause neurologic signs. Phlebotomy for baseline bloodwork was performed, and intravenous lipid emulsion (ILE) was subsequently administered, for treatment of the suspected toxicosis. Due to severe and life-threatening neurologic signs, other methods of decontamination were contraindicated and unlikely to be effective; extracorporeal therapy was also unavailable. Complete resolution of neurologic signs occurred 30 minutes after completion of ILE therapy. At this time, the owners found the missing naproxen tablets after returning home and the bloodwork results returned revealing findings consistent with hepatic encephalopathy. The fasted blood ammonia concentration immediately prior to ILE administration was 702.1 µg/dL (reference interval, RI: 24-36 µg/dL) and decreased to 194.1 µg/dL 24 hours later. In the first 24 hours, the patient also received three doses of lactulose, N-acetylcysteine (NAC) and intravenous fluids. The patient was subsequently diagnosed with a single, large intrahepatic portosystemic shunt via computed tomography and underwent an endovascular coil embolization procedure. Given the rapid and dramatic improvement in severe neurologic signs after ILE therapy alone, it is strongly suspected that this treatment resulted in improvement of hepatic encephalopathy.